Análise da Metodologia da Pesquisa nas teses em Educação Matemática produzidas em programas brasileiros de pós-graduação - Alves dos Santos, Marluce (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
In this paper, I present the doctoral research on the analysis of research methodology in the theses in Mathematics Education produced in Brazilian graduate programs. To this end, I will discuss the research methodology as a constitutive and formative problem area. Below, we briefly present the contributions nationally and internationally on research in mathematics education. Indicate the importance of studying on knowledge, and aim for conducting a systematic review, a careful process of selection and exclusion of research in mathematics education in Brazil consolidated from mainly the 80’s, when the first programs were installed graduate of the country. So, could present a state of the art in the area, pointing out some weaknesses that need to be overcome and the successes that have been achieved.